Riding the green wave in the European agricultural sector? A discourse analysis of the new cross compliance mechanism - Meri Juntti (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2006)
This paper analyses the integration of environmental standards into the European Union's Common Agricultural Policy (CAP). It focuses on the negotiation of the new environmental cross compliance rules, which were incorporated in the CAP's 2003 mid-term review and which now define a baseline level of environmental protection that a farm needs to adhere to in order to receive agricultural subsidies. Cross compliance has been lauded as an important new mechanism for greening agriculture, a policy sector which is under increasing pressure to mitigate its environmental impact. Using a discourse oriented approach this paper sheds further light on this assertion by assessing how far cross compliance actually represents a shift in policy goals and priorities. It does so by outlining the premises of decision-making and the range of policy problems that cross compliance was perceived to address in the agricultural sector. The discourse approach highlights the critical importance of agenda setting in policy design, an area that has received little attention in literature on environmental policy integration. The analysis reveals that instead of conforming to a single dominant policy agenda which raises the status of environmental protection requirements, a number of conflicting agendas have influenced the design of the new mechanism. The results show how persisting agrarian as well as market oriented aspirations ride the wave created by pressure to green the sector. This raises doubts about the ability of cross compliance to deliver environmental outputs in practice.
Keywords: 330; Agricultural policy; cross compliance; discourse analysis; policy decision-making